UNDANG-UNDANG CIPTA KERJA DI TENGAH HIMPITAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020 - Irawan, Atang (Faculty of Law, Universitas Pasundan, 2022)
The Job Creation Act is believed to be able to end the obesity of statutory regulations in Indonesia which often creates disharmony between laws and regulations which results in sectoral ego and bureaucracy in providing government services to the people, both in the form of permit and non-permit. The spirit of the Job Creation Act in the context of regulatory simplification is expected to accelerate national economic recovery in the midst of a pandemic and to cut bureaucracy in services for investment and MSMEs. However, along the way, the Constitutional Court Decision No. 91/PUU-XVIII/2020 has stated that Law No. 11 of 2020 concerning Job Creation does not have conditionally binding legal force as long as it is not interpreted as